Enhancing Multidisciplinary Team Board Efficiency and Communication Using the SBAR Approach - Nazeer Ahmed; Ahmed Nadeem Abbasi; Zainab Farooq (Pakistan Journal of Medicine and Dentistry)
In oncology, healthcare professionals from different specialties, such as oncologists, radiologists, and surgeons, assemble to form a cooperative group described as the Multidisciplinary Team (MDT). Whose main objective is to formulate standardized Treatment plans for cancer patients. MDTs are now widely used in the global healthcare system to manage complicated cases. Weekly MDT meetings have become a benchmark for cancer care. However, these meetings are often time-consuming, and challenging due to the diverse range of perspectives. This is where the SBAR communication tool comes into play1.